Changes in lactate kinetics underpin soccer performance adaptations to cycling-based sprint interval training. Issue 4 (20th April 2020) - Thom, Graham; Kavaliauskas, Mykolas; Babraj, John
Abstract: In adolescent soccer, 23% of the distance covers happens at speeds above onset of blood lactate accumulation which suggests that lactate kinetics may be important for soccer performance. We sought to determine the effectiveness of sprint interval training (SIT) on changing performance and lactate kinetics in adolescent soccer players. Thirteen elite soccer academy players (age 15 ± 0.5y) underwent baseline testing (0–10 m and 10–20 m sprint performance, Wingate anaerobic Test (WaNT) with blood lactate measurements and incremental VO2 peak test) before being allocated to control or SIT group. The control group maintained training whilst the HIT group carried out twice-weekly all-out effort cycle sprints consisting of 6 × 10 s sprint with 80 s recovery. There were significant time x group interactions for 10–20 m sprint time (Control pre: 1.32 ± 0.07 s post: 1.35 ± 0.08 s; SIT pre: 1.29 ± 0.04 s post: 1.25 ± 0.04 s; p  = 0.01), Peak Power (Control pre: 13.1 ± 1.3 W.kg −1 post: 13.2 ± 1.47 W.kg −1 ; SIT pre: 12.4 ± 1.3 W.kg −1 post: 15.3 ± 0.7 W.kg −1 ; p  = 0.01) and time to exhaustion (Control pre: 596 ± 62 s post: 562 ± 85 s; SIT pre: 655 ± 54 s post: 688 ± 55 s; p  = 0.001). The changes in performance were significantly correlated to changes in lactate kinetics (power: r  = 0.55; 10–20 m speed: r  = −0.54; time to exhaustion: r  = 0.55). Therefore, cycle based SIT is an effective training paradigm for elite adolescent soccer players and the improvements in performance are associated with changes in lactate kinetics.